High School Physics Teacher’s Profile In Teaching For Improving Student’s Energy Literacy - Soni Sukendar; Agus Setiawan (Journal of Science Education Research, 2018)
The research has been conducted to find out the profile of high school physics teacher in learning that develop student energy literacy. The method used in the research is descriptive-analytics using questionnaires that are distributed to high school physics teachers in MGMP district/city. The data are energy literacy understanding, energy literacy implementation in daily life, ability in developing learning, obstacles, and training needs. Based on the results of data analysis, it can be concluded that high school physics teacher has not yet understood the concept of energy literacy, although it has been implemented in daily life. Physics learning has not yet developed student energy literacy. Therefore it is necessary to develop blended training mode in MGMP.